BERENGAR AND THE VIRGIN-BIRTH - Macdonald, A. J. (The journal of theological studies, 1929)
A. J. MACDONALD; BERENGAR AND THE VIRGIN-BIRTH, The Journal of Theological Studies, Volume os-XXX, Issue April, 1 April 1929, Pages 291–294, https://doi.org/10.